A 114% Cigarette Tax Hike and Drinking Behavior: Results From Nationally Representative Longitudinal Panel Data in Korea. (September 2022) - Lee, Boram; Seo, Dong-Chul
This study investigated whether or not drinking behavior changed among Korean adult smokers after a 114% cigarette tax hike in 2015. Data were drawn from waves 9 to 12 (collected yearly from 2014 to 2017) of the nationally representative longitudinal study, the Korean Welfare Panel Study. Korean adults who were ≥19 years comprised the analysis sample (N = 10 875). We applied a difference-in-differences approach to compare drinking behavior before and after the tax increase among three groups (i.e., quitters, continued smokers, and nonsmokers). We found that alcohol drinking significantly decreased among those who quit smoking after the tax increase, compared with nonsmokers ( P = .022). Our findings support that a cigarette tax increase may have the beneficial spillover influence of reduction in drinking as well as smoking if the tax increase can induce smokers to quit, but such positive spillover influence may be short-term or null for continued smokers.